1999
DOI: 10.1038/sj.bjp.0702355
|View full text |Cite
|
Sign up to set email alerts
|

Endothelium‐derived relaxing, contracting and hyperpolarizing factors of mesenteric arteries of hypertensive and normotensive rats

Abstract: 1 Di erences in the acetylcholine (ACh)-induced endothelium-dependent relaxation and hyperpolarization of the mesenteric arteries of Wistar Kyoto rats (WKY) and stroke-prone spontaneously hypertensive rats (SHRSP) were studied. 2 Relaxation was impaired in preparations from SHRSP and tendency to reverse the relaxation was observed at high concentrations of ACh in these preparations. 3 Relaxation was partly blocked by N G -nitro-L-arginine (L-NOARG, 100 mM) and, in the presence of L-NOARG, tendency to reverse t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
49
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 40 publications
(75 reference statements)
8
49
0
1
Order By: Relevance
“…Acetylcholine-mediated relaxation was observed in 75% of vessels. Because endothelium-derived hyperpolarization is responsible for acetylcholine-induced responses in NO-blocked, human renal interlobar arteries 22 and K + -depolarization attenuates the response to acetylcholine compared with agonists, 23 the present data may have underestimated the functional state of the endothelium and the relaxing effect of PGI 2 and prostacyclin because membrane potential is clamped in response to elevated K + . The relaxation induced by prostacyclin was blocked by an IP receptor antagonist; the response was independent of the functional state of the endothelium, and IP mRNA and protein were detected in intrarenal arteries.…”
Section: Discussionmentioning
confidence: 72%
“…Acetylcholine-mediated relaxation was observed in 75% of vessels. Because endothelium-derived hyperpolarization is responsible for acetylcholine-induced responses in NO-blocked, human renal interlobar arteries 22 and K + -depolarization attenuates the response to acetylcholine compared with agonists, 23 the present data may have underestimated the functional state of the endothelium and the relaxing effect of PGI 2 and prostacyclin because membrane potential is clamped in response to elevated K + . The relaxation induced by prostacyclin was blocked by an IP receptor antagonist; the response was independent of the functional state of the endothelium, and IP mRNA and protein were detected in intrarenal arteries.…”
Section: Discussionmentioning
confidence: 72%
“…Data are shown as mean SEM. experimental design (isometric, isobaric contractions) and the type of precontraction drugs that were used (norepinephrine, phenylephrine, 5-HT) (18)(19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…There was a loss of the K ϩ channel pathway in small arteries from hypertensive rats, which is consistent with previous reports in small mesenteric arteries in SHR and ANG rats. 10,[31][32][33][34][35] Studies that have assessed EDHF-and NOS-mediated dilation in mesenteric resistance arteries from hypertensive rats and mice report decreased NO and/or EDHF contributions to relaxation in mesenteric arteries. 12,[32][33][34][35] Although it is very difficult to compare these studies because of differences in experimental protocols and/or animal models, many of these studies observed an imbalance of the EDHF and/or NOS pathways in the vasodilator response.…”
Section: Endothelial Dysfunction In Large and Small Arteries Is Distinctmentioning
confidence: 99%